Empowerment of Local Workers at CV. Amg Farm and Food Garden Banjar Manik Gunung Selanbawak Village Marga District Tabanan Regency - Ni Gusti Ketut Sri astiti; Desak Gde Dwi Arini; Nengah Ganawati; Ni Made Dwi Wulandari; Dwi Nova Indriyani (Fakultas Hukum, Universitas Warmadewa, 2023)
As an institution of higher education, Warmadewa University must be able to ensure that it always obeys the Tri Dharma of Higher Education in accordance with the vision and mission that has been determined. Now every lecturer is encouraged to be able to package community service activities both in groups and individually which will show concern for the community. Community service activities can be carried out by enlightening by providing legal counseling and consultation, socialization and assistance to the community in various fields of life in the economic field. One of the things that should be observed in the service carried out at CV. AMG Farm and Food Garden Banjar Manik Gunung, Selanbawak Village, Marga District, Tabanan Regency, with the existence of an organic culinary business must empower local workers to the surrounding community because it has a high potential for business development. Realizing the importance of workers for the Company, Government and Community, it is necessary to think so that workers can maintain their safety in carrying out their work. In the implementation of development, workers have an important role and meaning as a supporting element for the success of national development in general and regional development in particular. The main objective of this research is to address the challenges faced by the organic culinary business CV. AMG Farm and Food Garden Banjar Manik Gunung Selanbawak Village, Marga District, Tabanan Regency. The method of data collection that uses in this Program are Semi-Structured Interviews and Focus Group Discussions.